Pengaruh Brand Image dan Product Quality terhadap Repurchase Intention : Customer Satisfaction sebagai Variabel Mediasi ( Studi pada Pelanggan Clodia Outfit Malang ) - Shelza Tirta Fadilah; Nur Hidayati; Mohamad Bastomi (UNIVERSITAS ISLAM MALANG, 2026)
Abstract This study aims to analyze the effect of Brand Image and Product Quality on Repurchase Intention with Customer Satisfaction as a mediating variable among Clodia Outfit Malang customers. This study uses quantitative research with an explanatory approach. Data were collected using a survey method with a sample of 120 respondents, with the population being Clodia Outfit customers in Malang City. Data were analyzed using the Structural Equation Modeling (SEM-PLS) method with the help of Smart PLS 4.0 software. The results show that brand image does not have a significant effect on customer satisfaction, product quality has a significant effect on customer satisfaction, brand image has a significant effect on repurchase intention, product quality has a significant effect on repurchase intention, customer satisfaction has a significant effect on repurchase intention, customer satisfaction is not able to mediate the effect of brand image on repurchase intention, and customer satisfaction is able to mediate the effect of product quality on repurchase intention. Keywords: fashion; brand image; product quality; customer satisfaction; repurchase intention